PO.7.144 ASSESSLE- a new tool to assess sle disease activity- the patients' perspective. (27th September 2022) - Paran, D; Ben-Am, M; Mendel, L; Ari, P; Furer, V; Elalouf, O; Wollman, J; Eviatar, T; Pel, S; Kivity, S; Elkayam, O; Agmon-Levin, N
Abstract : Purpose: Systemic lupus erythematosus (SLE) is a heterogeneous, waxing and waning, multisystem autoimmune disease. The complexity and clinical unpredictability of SLE challenge the assessment of disease activity over time, especially in every day clinical practice. Multiple clinical disease monitoring instruments have been developed, however they are limited in ability to detect change in disease activity over time, too cumbersome to be utilized in daily practice and do not include patient reported outcomes (PROs). We aimed to construct a new disease activity score which will simplify and improve disease activity assessment in daily practice, and include PROs. Here we present the PRO component. Methods: The new instrument for the assessment of SLE activity is comprised of 7 visual analogue scales (VAS), which separately address the physician's global assessment and 6 organ systems. The PRO consists of 5 VAS questions which address general well-being, global disease activity, activities of daily living, medication compliance and mood. The ASSESSLE PRO is compared to the Short Form Health Survey (SF-36) which is a 36-item, patient reported survey of patient health. We applied the ASSESSLE PRO to 46 consecutive patients with SLE attending the rheumatology clinic in 2 tertiary medical centers in Israel. Results: Psychometric evaluation of the reliability of all 5 PRO questions indicated that question 4, regarding compliance, poorly correlated with the other items and lowered the reliability (Cronbach's α =0.80 95% CI [0.74, 0.85]). Following omission of question 4, Cronbach's α was recalculated, leading to increased internal reliability (Cronbach's α = 0.86, 95% CI [0.82, 0.90]). All other remaining items had satisfactory correlation with the other items ('item-other' correlation between 0.58–0.70). Therefore, the score was computed as the mean of the 4 remaining questions. Aiming to compare the ASSESSLE PRO to the SF-36 survey, Spearman correlation coefficient between absolute scores was computed and a strong and significant effect was found (R=0.85, p<0.0001) ( figure 1 ). Conclusions: The ASSESSLE PRO is a short PRO which allows a reliable, reproducible and simple PRO form showing excellent correlation with the SF-36. Following omission of question 4, regarding patient compliance, the ASSESSLE PRO consists of only 4 questions, as compared to the SF-36 which requires a response to 36 items. The ASSESSLE PRO seems to have significant advantages due to its intuitive VAS questions and brevity which allows use of this PRO in every day practice and may increase validity of disease activity evaluation of SLE when combined with the physician's assessment.